The Role of The Learning Cycle Method in The Form of Entrepreneurial Behavior in Early Childhood - Santa Murni A. Situmorang (Jurnal Usia Dini, 2017)
Entrepreneurship has essence of a good character which is expected to be the driving force of the nation’s development.  Entrepreneurship is taught not to lead the child to be an entrepreneur, yet it is rather to form the basic behavior that is in the soul of an entrepreneur and it can be formed through a learning process.  This paper discusses about theory of learning cycle method and its roles to form the entrepreneurial behavior on early childhood.  There are several variations of learning cycle method that can potentially form the entrepreneurial behavior.  Keywords: entrepreneurship, entrepreneurial behavior, learning cycle method